Local Climatological Data Summary: Fairfield, Illinois, 1901-1990 - Bryan, Audrey A.; Armstrong, Wayne (Illinois State Water Survey, 1991)
Fairfield (Wayne County) has a temperate continental climate, dominated by maritime tropical air from the Gulf of Mexico from about March through November. Gulf air generally supports relative humidities of about 60% during the day and 85% at night. During these months, there are occasional, brief interruptions of drier, cooler air from the Pacific Ocean, but typically only last for a few days. From November through March, the Fairfield area is dominated by Pacific Ocean air. Four to six times each winter, cold, dry air from the Canadian Arctic breaks south, bringing temperatures into the teens and even units. Average annual precipitation is about 44.94 inches. The highest temperature on record is 113°F recorded on 22 July 1901, whereas the lowest is -23°F occurring on 17 January 1977. is peer reviewed Submitted by Agnes Stankiewicz (stankie2@illinois.edu) on 2014-10-29T15:02:35Z No. of bitstreams: 1 ISWSMP-98-6.pdf: 355313 bytes, checksum: 60bf1395ca7a1ae4fc0659e63ee1f0e0 (MD5) Made available in DSpace on 2014-10-29T15:02:35Z (GMT). No. of bitstreams: 1 ISWSMP-98-6.pdf: 355313 bytes, checksum: 60bf1395ca7a1ae4fc0659e63ee1f0e0 (MD5) Previous issue date: 1991 published or submitted for publication Open